EGFR Mutation and Neutrophil-Lymphocyte Ratio as Prognostic Biomarkers in Lung Adenocarcinoma: Insights from Western India - Chag, Shyama Manojkumar; Kansara, Khevna Mayurkumar; Gupta, Monica Vikas; Asarawala, Nirav Niranjanbhai (Annals of Pathology and Laboratory Medicine, 2025)
Background: Lung adenocarcinoma is a heterogeneous malignancy where epidermal growth factor receptor (EGFR) mutations and systemic inflammation markers like neutrophil-to-lymphocyte ratio (NLR) serve as crucial prognostic tools. Our objective is to analyze the prevalence and types of EGFR mutations, correlation with addiction and histomorphological patterns, and evaluate the prognostic impact of NLR on progression-free survival (PFS) and overall survival (OS). Methods: This observational study was conducted at a tertiary care center in Gujarat, including 317 cases of lung adenocarcinoma from 2018-2024. EGFR mutation testing was performed on 113 cases using PCR and pyrosequencing. NLR was derived from baseline blood counts and categorized using Youden's index-derived ROC cut-off (2.89). Kaplan-Meier survival analysis and Cox regression were employed to assess outcomes. Result: EGFR mutations were detected in 36/113 cases (31.8%), more frequently in females (53%) than males (23%). Exon 19 deletions were the most common (66.7%). A significant association was found between EGFR mutation and non-addiction status (p=0.019). Glandular histology predominated among both mutated (58.3%) and wild-type (80.5%) cases. High-NLR status (≥2.89) was significantly associated with shorter PFS (median ≈10 vs ≈19 months, HR 1.44, p=0.23). OS was shorter in high-NLR cases (median ≈11 vs ≈24 months, HR 1.51, p=0.18). Conclusion: EGFR mutations are more prevalent in non-smoking females and are associated with specific histological subtypes. Elevated NLR is a strong predictor of poor PFS, reinforcing its utility as a prognostic biomarker in lung adenocarcinoma. Integrating EGFR and NLR status into diagnostic protocols can enhance individualized management strategies.